Psychometric Validity of the Areas of Work Life Scale (AWS) in Teachers and Healthcare Workers in México - Arturo Juárez-García; César Merino-Soto; Javier García-Rivas (MDPI AG, 2023)
The areas of work life scale (AWS) has shown to be a suitable marker of perceived fit between employees' abilities and the psychosocial demands of the job, but validation studies are practically nonexistent in the Latino population. The purpose of this study was twofold: firstly, to examine the factor structure, reliability, and invariance between sex and occupation of the AWS scale, and secondly, to test the AWS-burnout relationship within the framework of the structural mediational model proposed by Leiter and Maslach (2005). N = 305 health workers and N = 324 teachers from different work settings answered the AWS and MBI-GS scales. In this study, 64.4% of the participants were females (N = 405), and the mean age was 34.7 (sd = 11.7, rank = 56). Robust methods for statistical analyses were used. The results showed that the original version had marginal fit indices due to a method effect (negative phrasing items), and when seven negative items were removed, a final best model was found (CFI = 0.997; RMSEA = 0.060; SRMRu = 0.047). Non-invariance between occupation and sex was found, and the internal consistency was from marginal to satisfactory (ω = 0.658 to 0.840). The mediational structural model tested confirmed the expected associations between AWS and burnout. In conclusion, the Mexican translation of the AWS in its 22-reduced version showed reliability and validity in Mexican work contexts, specifically in healthcare workers and teachers.